Effectiveness of on-the-job learning for enterprises’ innovativeness - Kusum, P.P. Ajith; Yinghua, Song (International research journal of management, IT and social sciences, 2017)
The mode of on-the-job learning – one of the methods of acquiring competencies still remains one of the main modes of acquiring workplace competencies in conventional industries in developing countries. This paper explores the impact of aforesaid mode of competency acquisition for enterprise innovativeness of an industry of Sri Lanka. A structured questionnaire was used to gather primary data related to modes of acquiring competencies. Before data collection, it was reviewed by industry experts and piloted later on for validity. The paper analyses and presents the effectiveness of on-the-job learning on the innovativeness of enterprises in this industry. The research has found that the main mode of acquiring enterprise competencies remains on-the-job learning. It has been found that the level of innovations in enterprises in the industry remains at low attributed to the traditional way of acquiring competencies. As a result, the industry stagnates and faces challenges for sustainability. No similar research study was done before in this industry and this is an original work. The study has implications to policy, theoretical and practical aspects of the industry.